2017
DOI: 10.24893/jkma.v10i1.161
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Kejadian Preeklampsia Pada Ibu Hamil Di Rsup Dr. M. Djamil Padang Tahun 2014

Abstract: AbstrakPreeklampsia merupakan penyakit yang disebabkan kehamilan dan penyebab kematian maternal. Angka kejadian preeklampsia di RSUP. DR. M. Djamil Padang Tahun 2014 adalah 20,14%. Tujuan penelitian ini mengetahui faktor risiko yang berhubungan dengan kejadian preeklampsia pada ibu hamil di RSUP DR. M. Djamil Padang tahun 2014. Jenis penelitian observasional analitik dengan rancangan kasus kontrol. Jumlah sampel 34 kasus dan 34 kontrol, perbandingan 1:1. Pengambilan sampel menggunakan teknik systematic random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
2
5
0
5
Order By: Relevance
“…In this study sample, the number of pregnant women with nulliparous and primigravida was less than those who were not. This study was in line with previous studies 8,17 .Likewise, with the research of Shamsi et al 10 , the number of nulliparous women was less and not much different from the number of non-nulliparous women, and statistically showed that parity had no significant relation with the incidence of preeclampsia (p = 0.915). However, this result was different from the study conducted by Khader et al 13 .…”
Section: The Relation Of Maternal Characteristic and Preeclampsia Incidencesupporting
confidence: 92%
“…In this study sample, the number of pregnant women with nulliparous and primigravida was less than those who were not. This study was in line with previous studies 8,17 .Likewise, with the research of Shamsi et al 10 , the number of nulliparous women was less and not much different from the number of non-nulliparous women, and statistically showed that parity had no significant relation with the incidence of preeclampsia (p = 0.915). However, this result was different from the study conducted by Khader et al 13 .…”
Section: The Relation Of Maternal Characteristic and Preeclampsia Incidencesupporting
confidence: 92%
“…Nursal's 2016 study explained that the risk-aged group (55.9%), which means pregnant women aged <20 years and >35 years are at high risk for experiencing glamorous disease occurrences compared to age 20 to 35. This has happened because at age <20 and >35 years old mother has experienced an increase or a decline in reproductive system function [8].…”
Section: Discussionmentioning
confidence: 99%
“…Age>35years or age is experiencing a decline in reproductive system as mothers age are sustained to disease as easily increased blood pressure. Pregnant mothers at a high risk of checks for antenatal care are very important to detect early detection, and prevent the possibility of suffering from accompanied disease during pregnancy [8]. Based on the results of a mothers age study that is still young and too old in pregnancy can increase the risk of chronic diseases such as DM, heart disease, hypertension, preeclampsia, and eclampsia due to the fact that the mother is a teenager ICHT 2019 or old woman does not consume good nutrition, although the nutrients that the mother consumes are strongly affecting the fetus condition [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salah satu faktor risiko kejadian preeklampsia adalah umur (Nursal, Tamela, & Fitrayeni, 2017 pendidikan terekahir tinggi dengan nilai p = 0,011 < α = 0,05.…”
unclassified